Empowering Preschool Teachers: Excel Mastery for Report Writing and Teaching Module Development - Arie Purwa Kusuma; Deswita Deswita; Lubban Anwari Alhamidi; Nurina Kurniasari Rahmawati; Rifa Atiyyah (FOUNDAE (Foundation of Advanced Education), 2024)
Early childhood education is one of the most basic levels of education for children's growth and development. Teachers who provide education for early childhood are required to have a special level of education and competence in compiling teaching modules for learning activities. Information technology literacy supports teachers in solving administrative problems. One of the administrative things that teachers routinely do is make report cards for their students. Using Microsoft Excel software has many features and functions that can help in creating reports. Apart from that, teaching materials in learning need to be considered, including teaching modules which must be developed by teachers themselves to suit the environmental context and learning needs of their students, including teachers in Early Childhood Education (PAUD). The aim of this service is to create teaching modules for learning activities. The method used in the activity was training using lecture, question and answer and discussion methods, with a total of 156 participants which was carried out over two days. Through this activity, participants' skills and understanding increased regarding the use of Microsoft Excel software and all teachers understood more about teaching modules, preparation steps and the use of Excel in making report cards.